THE EFFECT OF SERVANT LEADERSHIP, ORGANIZATIONAL CULTURE AND COMPENSATION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) OF TRANSPORTATION SERVICE EMPLOYEES OF BARITO KUALA REGENCY IN MARABAHAN - Muhammad Abduh; Rediyono, Rediyono (SEAN Institute, 2021)
This study aims to determine and analyze the influence of Servant Leadership , Organizational Culture and Compensation simultaneously on Organizational Citizenship Behavior (OCB) of Employees of the Barito Kuala Regency Transportation Agency in Marabahan. To determine and analyze the influence of Servant Leadership , Organizational Culture and Compensation partially on Organizational Citizenship Behavior (OCB) of Employees of the Barito Kuala Regency Transportation Agency in Marabahan. To determine the variables of Servant Leadership , Organizational Culture and Compensation that have a dominant influence on Organizational Citizenship Behavior (OCB) of Employees of the Barito Kuala Regency Transportation Agency in Marabahan. The data analysis method uses a quantitative method , this type of research is included in the type of explanatory research, science can be classified as a type of causal research, namely research that wants to find an explanation in the form of a cause-effect relationship between several concepts or several variables. The results of the study show that Servant Leadership has a partial significant effect on the Organizational Citizenship Behavior (OCB) variable. Culture Organization partially has a significant influence on the Organizational Citizenship Behavior variable (OCB). Compensation partially has a significant effect on the Organizational Citizenship Behavior (OCB) variable. Servant Leadership , Organizational Culture and Compensation have a significant effect simultaneously on the Organizational Citizenship Behavior (OCB) of the Barito Kuala Regency Transportation Agency in Marabahan. Variables that have an effect dominant towards Organizational Citizenship Behavior (OCB) is variable Servant Leadership. This means that the better the implementation of servant leadership in the organization by the leaders, the better the tendency for the implementation of organizational citizenship behavior by employees.